Nanocomposite hydrogels: Fracture toughness and energy dissipation mechanisms. Issue 24 (8th October 2015) - Klein, Andrea; Whitten, Philip G.; Resch, Katharina; Pinter, Gerald
ABSTRACT: In this study, fracture toughness of nanocomposite hydrogels is quantified, and active mechanisms for dissipation of energy of nanocomposite hydrogels are ascertained. Poly( N, N ‐dimethylacrylamide) nanocomposite hydrogels are prepared by in situ free radical polymerization with the incorporation of Laponite, a hectorite synthetic clay. Transmission electron microscopy proves exfoliation of clay platelets that serve as multifunctional crosslinkers in the created physical network. Extraordinary high fracture energies of up to 6800 J m −2 are determined by the pure shear test approach, which shows that these soft and stretchable hydrogels are insensitive to notches. In contrast to single‐ and double‐network hydrogels, dynamic mechanic analysis and stress relaxation experiments clarify that significant viscoelastic dissipation occurs during deformation of nanocomposite hydrogels. Similar to double‐network hydrogels, crack tip blunting and plastic deformation also contribute to the observed massive fracture energies. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2015, 53, 1763–1773 Abstract : The fracture energy of poly( N, N ‐dimethylacrylamide)‐Laponite XLS nanocomposite hydrogels was quantified by the pure shear test to be up to 6800 J m −2, the second highest reported for a hydrogel. Crack tip blunting, plastic deformation, and viscoelastic dissipation cooperate to achieve extraordinary high fracture energies.